From Imitation to Collusion - A Comment - Jörg Oechssler; Alex Roomets; Stefan Roth (University of Heidelberg, Department of Economics, 2015)
In oligopoly, imitating the most successful competitor yields very competitive outcomes. This theoretical prediction has been confirmed experimentally by a number of studies. A recent paper by Friedman et al. (2015) qualifies those results in an interesting way: while they replicate the very competitive results for the first 25 to 50 periods, they show that when using a much longer time horizon of 1200 periods, results slowly turn to more and more collusive outcomes. We replicate their result for duopolies. However, with 4 firms none of our oligopolies becomes permanently collusive. Instead, the average quantity always stays above the Cournot-Nash equilibrium quantity. Thus, it seems that "four remain many" even with 1200 periods.
urn:nbn:de:bsz:16-heidok-185793
Keywords: 330; imitation; experiment